1961
DOI: 10.4141/cjps61-119
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Gamma Radiation on Stored Onions

Abstract: Gamma radiation doses of 3200, 4700, 6500, 7900 and 9500 rad completely inhibited sprouting of Brigham Yellow Globe onions in a 300-day test period during which 75 per cent of the non-irradiated controls sprouted. In a second test of equal duration, using controlled temperature storage and shed storage, less than 3 per cent of Autumn Spice onions exposed to either 4000 or 8000 rad sprouted, whereas more than 79 per cent of the non-irradiated bulbs sprouted. Irradiation reduced sprouting of Yellow Sweet Spanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

1966
1966
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
2
2
0
1
Order By: Relevance
“…The above-mentioned results were in accordance with those of Nuttall et al (16), Lewis and Mathur (12), and Kepkowa (9) working with irradiated onion bulbs. Tewfic^ reported that spraying of garlic with MH before harvest caused a reduction of disease during storage and improved the quality of the bulbs.…”
Section: E M Aciation O F Cloves During Storage Is One O F the M Ostsupporting
confidence: 91%
See 2 more Smart Citations
“…The above-mentioned results were in accordance with those of Nuttall et al (16), Lewis and Mathur (12), and Kepkowa (9) working with irradiated onion bulbs. Tewfic^ reported that spraying of garlic with MH before harvest caused a reduction of disease during storage and improved the quality of the bulbs.…”
Section: E M Aciation O F Cloves During Storage Is One O F the M Ostsupporting
confidence: 91%
“…Moreover, the brown leaves increased in length throughout the storage period. Browning was also observed by Nuttal et al (16) and by Hori et al (7) in the inner buds of onions.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Several investigations involving botanicals follow. Nuttall et al (1961) found that yellow sweet Spanish onions exposed to 4000 or 8000 rad prevented sprouting in 97% of their experimental group suggesting that irradiation might be a viable method of prolonging storage life for onions. This study, while intriguing, has not been generally accepted by a public concerned with the problems of radiation.…”
Section: The History Of Gamma Radiation As Applied To Biological Systemsmentioning
confidence: 98%
“…Cependant, les oignons traités au champ ou avant entreposage avec des inhibiteurs de germination, tels que l'hydrazide maléique ou l'irradiation aux rayons gamma, peuvent demeurer indéfiniment à l'état latent (78,124). C'est ainsi que leur durée d'entreposage est prolongée de 8 à 10 mois selon l'efficacité du traitement, le cultivar des oignons, la présence de maladies et le procédé de séchage des bulbes.…”
Section: Oignons Séchésunclassified